STRATEGI KOMUNIKASI, INFORMASI, DAN EDUKASI (KIE) KADER DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DI POSYANDU VIRGO 6 KABUPATEN BEKASI - Sabila, Siti Zahra; Sutarjo, Sutarjo; Santika, Tika (Comm-Edu (Community Education Journal), 2025)
This study aims to describe the strategies of communication, information, and education (KIE) implemented by health cadres in increasing community participation at Posyandu Virgo 6, Bekasi Regency, and to identify the challenges encountered during implementation. A descriptive qualitative approach was used, with data collected through observation, in-depth interviews, and documentation. The informants included the head of the cadres, two cadre members, and two posyandu participants. The results showed that KIE strategies were carried out through interpersonal, educative, participatory, and adaptive approaches. Communication was conducted directly using simple language, visual media such as posters and the maternal and child health (KIA) book, and dialogue-based education. These strategies proved effective in raising awareness and increasing community attendance. However, cadres faced several challenges, including limited understanding among some residents, shortage of cadre personnel, lack of educational media, and absence of supporting facilities such as toilets. Therefore, support from multiple parties, including cadres, community members, village government, and health workers, is needed to ensure that the implementation of KIE strategies at the posyandu can operate more effectively and sustainably.